Systems analysis of fragility in Cabo Delgado, Mozambique. - Minoarivelo, Onivola; Craparo, Alessandro; Basel, Ashleigh; Pacillo, Grazia; Laderach, Peter (2024)
Since the eruption of violence in October 2017 involving non-state armed groups and government forces in Cabo Delgado, the situation has remained volatile in the region. As the conflict crisis is compounded by recurrent tropical cyclones, heavy rains and drought, over 1.7 million people are still requiring critical humanitarian assistance in this province as of the start of 2024. WFP’s largest operation in Mozambique is in this province. To support WFP’s operations, CGIAR conducted a systems analysis of conflict and fragility in Cabo Delgado. First, with a spatiotemporal co-occurrence analysis of climate hazards and conflicts across the broader region, we show that Mozambique has been particularly exposed to high climate hazards and conflicts over the past three decades, while climate hazards are expected to increase to extreme levels by 2040. Second, by performing a conflict-sensitivity analysis for Mozambique with a special focus on Cabo Delgado, we emphasize the severity of conflict impacts and exposure in this region. Finally, using a compound risk framework (CRF) tailored for Cabo Delgado, we offer a comprehensive understanding of fragility in the province, highlighting conflicts and climate hazards as intricate drivers of acute food insecurity. The CRF reveals that critical factors preventing the escalation of instability through food insecurity include trade flows, alongside crop production. With a complex setting such as Cabo Delgado, the CRF emphasizes the significance of adopting systems approaches that can proactively identify high-risk areas, enabling more effective implementation of targeted interventions to enhance resilience.